2014
DOI: 10.1039/c4ra11156g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of TiO2 nanotube supported Rh-nanoparticle catalysts for regioselective hydroformylation of vinyl acetate

Abstract: Three procedures: the impregnation-borohydride reduction procedure, the impregnation-alcohol reduction procedure and the impregnation-photoreducing procedure, were utilized for preparing TiO2 nanotube supported rhodium nanoparticle catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…The results are shown in Figure 4. Compared with the peaks of Rh 0 (3d5/2 = 307.2 eV; 3d3/2 = 312.0 eV) in the reported Rh/TNTs [42], the peaks of Rh 0 in Au0.52/Rh0.32/TNTs-12 and Au0.49/Rh0.33/TNTs-22 ( Figure 4A,B) shift to a lower BE value (3d5/2 = 306.9 eV; 3d3/2 = 311.8 eV). The characteristic photoelectron peaks of Au 4f in both catalysts are displayed in Figure 4C,D.…”
Section: As Shown Inmentioning
confidence: 73%
See 1 more Smart Citation
“…The results are shown in Figure 4. Compared with the peaks of Rh 0 (3d5/2 = 307.2 eV; 3d3/2 = 312.0 eV) in the reported Rh/TNTs [42], the peaks of Rh 0 in Au0.52/Rh0.32/TNTs-12 and Au0.49/Rh0.33/TNTs-22 ( Figure 4A,B) shift to a lower BE value (3d5/2 = 306.9 eV; 3d3/2 = 311.8 eV). The characteristic photoelectron peaks of Au 4f in both catalysts are displayed in Figure 4C,D.…”
Section: As Shown Inmentioning
confidence: 73%
“…In our previous work [41], we found that the Rh-Ru/TNTs bimetallic catalysts with two types of active sites showed satisfactory catalytic performance in cyclohexene hydroformylation but poor selectivity for aldehydes in hydroformylation of vinyl acetate. The Rh/TNTs catalysts also exhibited a relatively lower selectivity for aldehydes [42]. In the present contribution, we designed the Au-Rh/TNTs catalysts for hydroformylation of vinyl acetate, in which gold is expected to provide more free coordination sites for substrates and work synergistically with rhodium to enhance the yield of aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…The assignment of the structure of titanate nanotubular was the subject of intense controversy [24]. In our previous report, the main diffraction peaks of TNTs were assigned as anatase phase of TiO 2 [9,25,26]. However, the samples indeed present four broad diffraction peaks located at 9.58 • , 24.36 • , 28.36 • , and 48.44 • which can be attributed to the (020), (110), (130), and (200) crystal planes of orthorhombic lepidocrocite-type titanate on the basis of literature [27][28][29].…”
Section: Characterization Of the Catalystsmentioning
confidence: 98%
“…Except the main peaks for the TNTs support, there is no any diffraction peaks related to Rh nanoparticles or other salts in all samples. This indicates that Rh nanoparticles or other salts in the as-prepared catalysts might be well dispersed on the support and the content of Rh nanoparticles or other salts might be too low to be detected by XRD technique [26].…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
“…[46] High regioselectivity towardi so-aldehyde wasr eported for the hydroformylation of vinyl acetate with Rh NPs stabilized in TiO 2 nanotubes. [47] The formation of soluble active species during hydroformylation was reported for Rh NPs stabilized by tetraoctylammoniumb romide. [48] We have previously reported excellent chemoselectivity to aldehydes at av ery high activity of the Rh catalyst in hydroformylation performed under water and solventless conditions.…”
Section: Introductionmentioning
confidence: 96%